ENKAPSULASI FRAKSI N-HEKSAN DAUN KESUM (Polygonum Minus Huds) TERSALUT Carboxymethylcellulose (CMC) DAN PATI DAN UJI AKTIVITAS ANTIOKSIDAN DENGAN TEKNIK FREEZE DRYING - Fitriani Fitriani; Muhammad Agus Wibowo; Andi Hairil Alimuddin (Indonesian Journal of Pure and Applied Chemistry, 2019)
Kesum have a scientific name Polygonum Minus Huds is one of the endemic plants originating from West Borneo.  Extracts of kesum leaf is easily damaged and the compounds contained therei are volatile. Therefore it is necessary to take measures to protect the extracts of kesum leaf. One effort that can be made to im exprove the stability of the compounds in the extract is by the process of encapsulation. This process needs to be done so that the leaf extract can last longer so it can be used for various purposes. Encapsulation aims to protect sensitive material components and reduce the degradation of the active compounds in the material. This study aims to determine the effect of mass of core materials on the efficiency of encapsulation and antioxidant activity and the effect of temperature on encapsulation. The results showed that the encapsulated with the mass of core material 10% gave the highest efficiency of 89.7%. The mass of the core material affects the encapsulation efficiency, the less the core material will provide a high value of encapsulation efficiency. Enkapsulates containing n-heksan fractions of 444.53 ppm have a lower value IC50, thus having better antioxidant activity properties. The stability of the encapsulated antioxidant activity performed at room temperature 25◦C at 10% n-hexane fraction yielded 88.36% ihibisi on day 1, 80.90% on day 3, 79.67% on day 6 and 78.04% on day 9. Activity the antioxidant encapsulant on the first day at room temperature 25◦C is better than the third, sixth and ninth days. SEM leaf extract analysis results have uneven spherical particles, no visible fracture or pore holes as large as encapsulation have round particles that are almost as large.